John Steinbeck and Terrence McNally on an European Tour - unknown:::Creator::::::::::::
John Steinbeck stands with Terrence McNally aboard the MV Saturnia, part of Societe di Navigazione Italia cruise line. McNally, who went on to receive five Tony Awards as a playwriter and a screenwriter, accompanied the Steinbecks as a tutor to John IV and Thomas. Original in safe